Women’s Language of Male Characters in Elemental Movie - Astari, Tjokorda Istri Agung Dyah; Aryawibawa, I Nyoman; Putra, Galuh Febri (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This undergraduate thesis is entitled